Interaction Model on Virtual Communication in Religious Narration in Digital Era - Andini, Andini (STAI AL-FALAH CICALENGKA, 2021)
This article was written as an initial note on determining attitudes in virtual communication related to religious narratives in the digital era. The digital world creates a virtual communication space that can be accessed by all people with different backgrounds. In addition, the digital world offers a religious narrative that is served like a buffet and this is often misused by parties or groups for personal gain. Communication which is built in the virtual world is free, anyone from various backgrounds is able to express opinions and information. This will lead to the fading of the values of religious authority, the strengthening of individualism, and the decrease of tolerance among religious people. Because religious narratives do not have clear power in terms of sources, sanad and authenticity of writing, which is worrying if consumed irresponsibly and results in extreme attitudes to understanding religious narratives. Determining the right attitude used in virtual communication is an important study in this paper. The point is to balance the flow of virtual communication that is not conducive, giving birth to a tolerant attitude in society in the digital world. Keywords: Virtual Communication, Religious Narrative, Digital Era Abstrak Artikel ini ditulis sebagai catatan awal tentang menentukan sikap dalam komunikasi virtual berkaitan dengan narasi keagamaan di era digital. Dunia digital menciptakan sebuah ruang komunikasi virtual yang dapat diakses oleh semua orang dengan latar belakang berbeda. Selain itu dunia digital menawarkan sebuah narasi keagamaan yang disajikan bagaikan prasmanan dan hal ini kerap kali disalahgunakan oleh pihak atau kelompok untuk kepentingan pribadi. Komunikasi yang dibangun dalam dunia virtual bersifat bebas, siapapun dari berbagai latar belakang mampu mengungkapkan pendapat dan informasi. Hal yang demikian akan membawa pada pudarnya nilai-nilai otoritas keagamaan, menguatnya individualism, dan menurunnya toleransi sesama umat beragama. Karena narasi keagamaan tidak memiliki kekuatan jelas dalam hal sumber, sanad dan keaslian tulisan, yang mengkhawatirkan jika dikonsumsi secara tidak bertanggung jawab dan berakibat pada sikap yang ekstrem memahami narasi keagamaan. Menentukan sikap yang tepat digunakan dalam komunikasi virtual adalah kajian penting dalam tulisan ini. Gunanya untuk penyeimbang arus komunikasi virtual yang tidak kondusif, melahirkan sikap toleran dalam masyarakat di dunia digital. Kata Kunci: Komunikasi Virtual, Narasi Keagamaan, Era Digital